Membranes and other extendons (p-branes) - Ne'eman, Yuval
Includes bibliographical references.; The interest in membranes and higher dimensional extended geometrical objects was inspired by the great successes of the string and superstring, first in 1968â€“73 as a theory of hadrons and then since 1984 as a â€œtheory of everythingâ€ â€” a unified theory of all interactions, including quantum gravity. In particular, membranes, â€œsupermembranesâ€ and â€œspinning membranesâ€ have been studied since 1985; an unexpected connection with supergravity opened in 1988 some new prospects for a quantized theory. General theorems about higher dimensional â€œp-branesâ€ or â€œextendonsâ€ were also derived. The subject is very promising, whether as a more comprehensive fundamental unification or as a description of composite hadrons.